Enhanced Mechanical and Thermal Properties of Waste Electric Porcelain-Based Solar Energy-Absorbing Thermal Storage Ceramics with Interwoven Mullite Structure - Xuejia Zhang; Zhenfei Lv; Junchi Weng; Mengke Fan; Feiyu Fan; Xin Wang; Xuyi Chen; Siqi Shi; Xiulin Shen (Crystals)
This study addresses the environmental and resource challenges posed by the growing volume of waste electric porcelain in the power industry by developing solar absorption and thermal storage integrated ceramics (SATS ceramics) from waste electric porcelain. These SATS ceramics, which feature an exceptional mullite structure, were crafted through the optimization of the sintering process. Notably, when sintered at 1400 °C with an 11 wt.% magnetite content, the resulting material boasts an optimal short-clustered, ordered, and interwoven columnar mullite structure. This structure endows the material with a remarkable flexural strength of 96.05 MPa and a specific heat capacity of up to 0.6415 J/(g* °C) at 300 °C, significantly enhancing its thermal energy storage efficiency. This research offers innovative insights into the high-value utilization of waste electric porcelain and the development of solar thermal storage materials, underscoring its significant environmental and economic advantages.